Hub GABA neurons mediate gamma-frequency oscillations at ictal-like event onset in the immature hippocampus - Quilichini, Pascale P. (2012)
Gamma-frequency oscillations (GFOs, > 40 Hz) are a general network signature at seizure onset at all stages of development, with possible deleterious consequences in the immature brain. At early developmental stages, the simultaneous occurrence of GFOs in different brain regions suggests the existence of a long-ranging synchronizing mechanism at seizure onset. Here, we show that hippocampo-septal (HS) neurons, which are GABA long-range projection neurons, are necessary to entrain hippocampal interneurons into transient high frequency firing at the onset of epileptiform discharges in the intact, immature septo-hippocampal formation. The synchronized firing of interneurons in turn produces GFOs, which are abolished after the elimination of a small number of HS neurons. Since they provide the necessary fast conduit for pacing large neuronal populations and display intra- and extrahippocampal long-range projections, HS neurons appear to belong to the class of hub cells, which play a crucial role in the synchronization of developing networks.